Features, applications, and sustainability of lipid nanoparticles in cosmeceuticals - Mohyeddin Assali; Abdel-Naser Zaid (Elsevier, 2022)
Cosmeceuticals are a branch of cosmetic products that forms a bridge between cosmetic and drug products. It is a fast-growing branch of the cosmetic industry, especially after the introduction of novel formulation and manufacturing techniques such as lipid nanoparticles (LNPs). These LNPs-based cosmeceutical products offer several advantages such as enhanced bioavailability of cosmeceutical active ingredients (CAIs), improved aesthetic appeal, and stability of the final products. However, the use of these LNPs may raise some concerns about possible side effects of these LNPs and potential hazards to the customer's health. Accordingly, an update that focuses on the use of this important branch of nanoparticles is necessary since most review papers are dealing with all types of nanocarriers in the same review with little focus on LNPs. Therefore, in the current review, a detailed analysis of the advantages and disadvantages of LNPs in this field was highlighted, to emphasize the LNPs-based cosmeceuticals on the market, as well as the potential risk posed by LNPs on exposure and recently introduced regulatory guidelines to address them. In addition, if these products can be a candidate as products that meet the sustainable development goals raised by the UN are discussed.